Diagnostic value of transoesophageal echocardiography in suspected haemodynamically significant pulmonary embolism. Issue 6 (1st June 2001) - Pruszczyk, P; Torbicki, A; Kuch-Wocial, A; Szulc, M; Pacho, R
Abstract : OBJECTIVE: To assess the value of transoesophageal echocardiography (TOE) for diagnosing suspected haemodynamically significant pulmonary embolism and signs of right ventricular overload at standard echocardiography. METHODS: 113 consecutive patients (58 male; 55 female), mean (SD) age 53.6 (13.3) years, in whom there was clinical suspicion of pulmonary embolism and right ventricular overload on transthoracic echocardiography, underwent TOE in addition to routine diagnostic procedures to identify pulmonary artery thrombi. RESULTS: TOE revealed thrombi in 32 of 51 patients who had suspected acute pulmonary embolism and in 31 of 62 with suspected chronic pulmonary embolism. In one patient a pulmonary angiosarcoma rather than chronic pulmonary embolism was found at surgery. The diagnosis of pulmonary embolism was confirmed in 77 patients by scintigraphy, spiral computed tomography, angiography, or necropsy (reference methods). While TOE failed to provide a diagnosis of pulmonary embolism in 15 of these 77 patients, no false positive findings were reported (sensitivity 80.5%, specificity 97.2%). In 11 and 26 cases, respectively, the thrombi were confined to the left or right pulmonary artery. Bilateral thrombi were found in 25 patients. Mobile thrombi were observed only in acute pulmonary embolism (in 19 of 32 patients). No complications of TOE were noted. CONCLUSIONS: TOE permits visualisation of pulmonary arterial thrombi, confirming the diagnosis in the majority of patients with pulmonary embolism and right ventricular overload. This may be useful for prompt decision making in patients with haemodynamic compromise considered for thrombolysis or embolectomy.